2013
DOI: 10.1210/en.2013-1179
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cisplatin-Induced Lipid Catabolism and Weight Loss by Ghrelin in Male Mice

Abstract: Cachexia, defined as an involuntary weight loss ≥ 5%, is a serious and dose-limiting side effect of chemotherapy that decreases survival in cancer patients. Alterations in lipid metabolism are thought to cause the lipodystrophy commonly associated with cachexia. Ghrelin has been proposed to ameliorate the alterations in lipid metabolism due to its orexigenic and anabolic properties. However, the mechanisms of action through which ghrelin could potentially ameliorate chemotherapy-associated cachexia have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 37 publications
11
104
0
Order By: Relevance
“…For example, amyotrophic lateral sclerosis (ALS) is characterized by the death of motor neurons and the atrophy of skeletal muscles, which leads to paralysis and death due to a lack of an efficient cure (Ludolph et al, 2012). During cancer, muscle atrophy may develop as a side effect of the chemotherapy (cisplatin, doxorubicin) (Gilliam and St. Clair, 2011;Hydock et al, 2011;Garcia et al, 2013) or at the late stage of the pathology (Fearon et al, 2012). This muscle-wasting syndrome (or cachexia) drastically reduces the patient's quality of life and may force the clinician to stop the treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, amyotrophic lateral sclerosis (ALS) is characterized by the death of motor neurons and the atrophy of skeletal muscles, which leads to paralysis and death due to a lack of an efficient cure (Ludolph et al, 2012). During cancer, muscle atrophy may develop as a side effect of the chemotherapy (cisplatin, doxorubicin) (Gilliam and St. Clair, 2011;Hydock et al, 2011;Garcia et al, 2013) or at the late stage of the pathology (Fearon et al, 2012). This muscle-wasting syndrome (or cachexia) drastically reduces the patient's quality of life and may force the clinician to stop the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, elevated ROS production has been linked to the presence of mutations in the ROS detoxification enzyme superoxide dismutase 1 (SOD1) associated with hereditary ALS (Beckman et al, 2001). Similarly, cisplatin and doxorubicin have been shown to induce the production of ROS (Chirino and Pedraza-Chaverri, 2009;Gilliam and St. Clair, 2011;Hydock et al, 2011;Garcia et al, 2013;Gilliam et al, 2013). ROS production has also been linked to the muscular atrophy induced by the presence of a tumor, likely mediated by cytokines, such as tumor necrosis factor-a (Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the weight loss observed 3 d after cisplatin administration (Table 3) is consistent with an earlier study which suggests cisplatin administration may lead to significant loss of body weight (Ö zdemir et al, 2002). The weight loss associated with cisplatin administration has been attributed to its stimulation of lipolysis and b-oxidation coupled with its suppression of lipogenesis (Garcia et al, 2013). Although the process through which sorghum straw red dye protects against cisplatin-induced weight loss cannot be categorically stated, it is suggested that anthocyanin and other polyphenol constituents of the red dye may be involved in the regulation of lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Anamorelin has been shown to have significant clinical, and patient-rated effects in cachexia associated with cancer [153].…”
Section: Anamorelinmentioning
confidence: 99%